2018
DOI: 10.1037/sgd0000275
|View full text |Cite
|
Sign up to set email alerts
|

Empirically based psychological interventions with sexual minority youth: A systematic review.

Abstract: Sexual minority youth (SMY, i.e., lesbian, gay, and bisexual individuals between the ages of 13–17) report increased rates of mental health concerns in comparison with heterosexual youth. However, there is a shortage of empirically supported treatments for SMY, as commonly administered interventions are understudied for minority communities. A systematic review of intervention literature was performed, consisting of 820 articles published through May 2017 that reported on intervention with SMY. After reviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 60 publications
1
42
0
3
Order By: Relevance
“…To date, there is a growing body of empirical support for a variety of affirmative, strength-based, and resiliency-oriented psychological interventions, models, and theoretical modalities (Hobaica et al 2018). Hobaica et al (2018) conducted a systematic review of empirically based psychological interventions for LGBTQ youth. This systematic review of 820 articles resulted in the identification of eight empirically supported interventions shown to be effective and suitable for LGBTQ youth.…”
Section: Lgbtq Help Seekingmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there is a growing body of empirical support for a variety of affirmative, strength-based, and resiliency-oriented psychological interventions, models, and theoretical modalities (Hobaica et al 2018). Hobaica et al (2018) conducted a systematic review of empirically based psychological interventions for LGBTQ youth. This systematic review of 820 articles resulted in the identification of eight empirically supported interventions shown to be effective and suitable for LGBTQ youth.…”
Section: Lgbtq Help Seekingmentioning
confidence: 99%
“…These interventions were also conducted in face-to-face, online, and computerized formats, although face-to-face was argued to have the most benefits. Accordingly, mental health and related professionals have access to a range of interventions and formats that can be utilized to address the complex issues of interpersonal violence in schools (Hobaica et al 2018).…”
Section: Lgbtq Help Seekingmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of psychosocial interventions for mental health problems amongst LGBT+ young people stated that only A few promising psychological therapies adapted to meet the needs of LGBTQIA [Lesbian, Gay, Bisexual, Transgender, Queer, Intersex and Asexual] individuals have emerged in recent years p [10]. This review from Van Der Pol-Harney and McAloon [10] and another review, conducted by Hobaica and colleagues [20], identified only one computerized intervention to support the mental health of LGBT+ young people, which was not focused on addressing drug usage, specifically Rainbow SPARX (Smart, Positive, Active, Realistic, X-factor thoughts) [10,20]. This intervention is a seven module cCBT program created for sexual minority young people from New Zealand [21], and is delivered in the English language.…”
Section: Introductionmentioning
confidence: 99%